2012
DOI: 10.1136/archdischild-2012-302724.1629
|View full text |Cite
|
Sign up to set email alerts
|

1629 Noise Pollution in Intensive Care Units and Emergency Wards

Abstract: Abstractsstayed as long as needed if they were functioning without evidence of local or systemic complications). Results 91 patients have had a total of 136 CVCs insertions. 112 temporary and 24 permanent catheters were evaluated for CLABSI whereas 73 CVCs were evaluated for CRBSI. Mean catheter days in group I was 11.95±12.48 and 20 cases of CLABSI were recorded in 1626 catheter days, given a CLABSI rate of 12.3:1000, whereas mean catheter days in group 2 was 9.30±5.23 with 1 case of CRBSI in 679 catheter day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…8 In the study Khademi et al was reported daily noise level was reached 94 dBA and mean daily noise intensity was 60.2 dBA. 9 So, the results from this study on daily noise levels were shown that there are similarity with other studies in literature.…”
Section: Discussionsupporting
confidence: 87%
“…8 In the study Khademi et al was reported daily noise level was reached 94 dBA and mean daily noise intensity was 60.2 dBA. 9 So, the results from this study on daily noise levels were shown that there are similarity with other studies in literature.…”
Section: Discussionsupporting
confidence: 87%
“…In intensive care units (ICUs), alarm‐sounding technological equipment, health team members and the patient's relatives are present (Terzi and Kaya, ), which together create a noisy environment (Khademi et al, ). Although various studies have investigated the effects of noise levels in health care organizations on patients (Akansel and Kaymakçı, ; Maidl‐Putz et al, ), studies investigating the effects of noise on nurses are limited (Ryherd et al, ; Lacerda Costa et al, ; Watson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Noise manifests itself especially in places such as hospitals where human traffic is busy and technological tools and equipment are used. It is stated that people working in hospitals are exposed to 87 dB(A) noise on average per day (Elliott et al, ; Khademi et al, ; Lacerda Costa et al, ). This level has been reported as being even higher in special units such as ICUs in which staff work for more than 8 h daily (Maidl‐Putz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Noise, defined as unwanted sounds, could affect people both psychologically and physiologically [7].Noise also has been defined as an accidental sound wave without any rhythm or harmony which can interfere with hearing [8]. To quantify sound levels, the decibel, an arithmetically non-dimensional linear scale, defines measured sound pressure [9,10], in which sound is measured as the force per unit area that sound waves produce.…”
Section: Introductionmentioning
confidence: 99%